Takhrij and Syarah Hadith of Chemistry: StudiesUtilization of Black Seed Plants as Herbal Medicines - Jajat Sudrajat; Moch Imron Taufiq; Rizka Fitriyani S; Mulyana Mulyana; Asep Saeful Mimbar (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the use of Black Seed. This research method is qualitative through the approach of takhrij and sharah hadith with analysis chemistry. The results and discussion of this research is that the use of Black Seed as medicine has become one of the options at the time of the Prophet, and is known in the world of modern medicine as one of the herbal medicines that are rich in benefits. The conclusion of this research is takhrij and syarah hadith of the Prophet about the benefits of Black Seed with chemical analysis has a very good role in a health perspective.